Long-term training in diabetes-related knowledge, attitudes, and self-reported practice among diabetes liaison nurses. Issue 2 (October 2020) - Zhou, Wen; Huang, Jin; Yang, Lingfeng; Qiu, Tieying; Zhang, Yan; Liu, Fang; Zhou, Zhiguang
Objective: We aimed to investigate whether long-term regular training of diabetes liaison nurses (DLNs) could improve their diabetes-related knowledge, attitudes, and self-reported practice. Methods: We enrolled 45 diabetes liaison nurses (DLNs) and 45 non-specialist nurses (controls). DLNs received 11 days of qualifying training, followed by regular theory classes and practice sessions for 4 years. All nurses were administered a questionnaire assessing demographic characteristics, knowledge about diabetes mellitus (DM), attitudes toward DM, and DM management practices, before and after the 4-year DLN training period. Results: At baseline, there were no significant differences between the DLN and control groups for sex, age, educational level, nurse title/grade, work experience, hospital department, or questionnaire scores. At 4 years, the DLN group had a higher overall questionnaire score and higher scores for knowledge about DM, attitudes toward DM, and DM management practices, as compared with baseline scores. Conclusion: Long-term regular training provided by a multidisciplinary diabetes care team can improve the knowledge, attitudes, and self-reported practice levels of DLNs.